The synergy of immersion and basic psychological needs satisfaction: Exploring gamification's impact on student engagement and learning outcomes - Bang Nguyen-Viet; Bac Nguyen-Viet (Acta Psychologica)
The integration of gamification into educational institutions has recently attracted considerable interest, owing to the digital era and emerging learning contexts. This study examined how immersion, an essential feature of games, affects various dimensions of education, including satisfaction of basic psychological needs (BPNS), academic engagement, perceived learning effectiveness, and perceived academic performance. Based on Self-determination Theory and the Theory of Gamified Learning, this study investigated how immersion influences autonomy, competence, and relatedness among learners, which could directly affect their engagement and outcomes. Quantitative findings derived from 568 respondent datasheets collected from university and postgraduate students in Vietnam indicate that immersion significantly influences BPNS. However, among the BPNS, only autonomy and competence affected engagement and learning outcomes. Using empirical research within the context of the post-COVID-19 Vietnamese education system, this study intends to provide useful insights for policymakers and researchers seeking to improve teaching performance by applying gamification in schools.